Influence of lower-extremity joint torque and power during vertical and horizontal jumps on swimming start performance in competitive swimming - Ikeda, Y.; Kawabe, M.; Hisamitsu, T. (The Journal of Strength and Conditioning Research, 2026)
Jumping ability plays a crucial role in optimizing kick start performance in swimming. However, effective training methods for transferring the enhanced jumping ability to the kick start movement remain unclear owing to insufficient understanding of the relationship between kick start and jump movements. This study explores the relationship between kinematic parameters during the kick start and leg muscular power output in horizontal and vertical jumps. Fourteen male competitive swimmers (20.2 ± 2.3 years) participated in the swim start and jump tests. Jump performance was evaluated using vertical jumps (VJ), squat jumps (SJ), and standing long jumps (SLJ). Key metrics included the jump height (VJ, SJ), horizontal distance (SLJ), take-off velocity, joint torques, and power output. The results showed that flight distance, influenced by the vertical velocity of the center of mass (CM) at take-off, was significantly correlated with 5-m and 10-m performance (P < 0.05). Jump performance metrics were notably associated with swim start parameters, highlighting the importance of jump direction. However, these metrics did not correspond to the vertical velocity of the CM at take-off during the kick start (r = -0.059-0.473, n.s). Swimmers with greater flight distances exhibited higher joint torques and power in the knee and ankle joints during jumps, as along with greater deviation of the CM take-off angle during the kick start. These findings suggest distinct technical requirements for enhancing both flight distance and CM horizontal velocity. Targeted resistance and plyometric training, combined with technical adjustments in CM positioning, may improve swimming start performance.